Computer Literacy im schulischen Kontext – eine internationale Perspektive - Eickelmann, Birgit (Bildung im Digitalen Zeitalter - Bilanz und Perspektiven)

Computer- und informationsbezogene Kompetenzen in der IEA-Studie ICILS 2013 und der Zusammenhang mit der Lesekompetenz - Eickelmann, Birgit; Drossel, Kerstin (Medienimpulse)

Abschlussbericht im Rahmen der wissenschaftlichen Begleitung der Evaluation des Projekts „Lernen mit digitalen Medien“ in Schleswig-Holstein - Gerick, Julia; Eickelmann, Birgit

Digitale Medien in Schule und Unterricht – Herausforderungen für die Schulentwicklung - Gerick, Julia; Eickelmann, Birgit; Rolff, Hans-Günter (Journal für Schulentwicklung)

Gelingensbedingungen für den Transfer schulischer Innovationen mit digitalen Medien. Ergebnisse aus einem Modellprojekt - Gerick, Julia; Eickelmann, Birgit; Ramm, Gesa; Kühn, Thore-Olaf (Journal für Schulentwicklung)

Schulische Medienkonzepte als Instrument der Schulentwicklung - Eickelmann, Birgit (Journal für Schulentwicklung)

Digitale Medien in Schule und Unterricht. Herausforderungen für die Schulentwicklung [Themenheft] (Journal für Schulentwicklung)

Lernaktivitäten mit digitalen Medien im Fachunterricht der Sekundarstufe I im Bundesländervergleich mit besonderem Fokus auf MINT-Fächer - Eickelmann, Birgit; Lorenz, Ramona; Endberg, Manuela (Schule digital – der Länderindikator 2017. Schulische Medienbildung in der Sekundarstufe I mit besonderem Fokus auf MINT-Fächer im Bundesländervergleich und Trends von 2015 bis 2017)

Unterrichtliche Nutzung digitaler Medien durch Lehrpersonen in der Sekundarstufe I im Bundesländervergleich und im Trend von 2015 bis 2017 - Lorenz, Ramona; Endberg, Manuela; Eickelmann, Birgit (Schule digital – der Länderindikator 2017. Schulische Medienbildung in der Sekundarstufe I mit besonderem Fokus auf MINT-Fächer im Bundesländervergleich und Trends von 2015 bis 2017)

Schule digital – der Länderindikator 2017. Schulische Medienbildung in der Sekundarstufe I mit besonderem Fokus auf MINT-Fächer im Bundesländervergleich und Trends von 2015 bis 2017

School-level predictors for the use of ICT in schools and students’ CIL in international comparison - Gerick, Julia; Eickelmann, Birgit; Bos, Wilfried (Large-scale Assessments in Education)

Predictors of teachers’ use of ICT in school – the relevance of school characteristics, teachers’ attitudes and teacher collaboration - Drossel, Kerstin; Eickelmann, Birgit; Gerick, Julia (Education and Information Technologies)

ICT use in mathematics lessons and the mathematics achievement of secondary school students by international comparison: Which role do school level factors play? - Eickelmann, Birgit; Gerick, Julia; Koop, Christian (Education and Information Technologies)

Teachers‘ attitudes and beliefs regarding ICT in teaching and learning in European countries - Eickelmann, Birgit; Vennemann, Mario (European Educational Research Journal)
In the debate on the integration of information and communication technologies (ICT) into schools, the beliefs and attitudes of teachers towards ICT in teaching and learning have always been regarded as central criteria for successful implementation of new technologies. In this context, a study in 2013 by the International Association for the Evaluation of Educational Achievement, IEA, provided insights into teachers’ beliefs regarding ICT and showed that perceptions of the pedagogical advantages of technologies differ between countries. With regard to this finding, this paper seeks to determine whether there is a typology of teachers with different attitudes towards the potential of ICTs for learning. This question is addressed by conducting latent class analyses on a sample of teacher data from three European countries – the Czech Republic, Germany and Norway. Furthermore, the paper investigates how the use of computers by teachers varies between the groups to which these teachers can be assigned. In doing so the research reported at hand connects, arguably for the first time, representative data on teacher typologies of attitudes towards and beliefs about ICT in teaching and learning with data on computer use in schools.

The international computer and information literacy study from a European perspective: Introduction to the Special Issue - Gerick, Julia; Eickelmann, Birgit; Bos, Wilfried (European Educational Research Journal)
The International Computer and Information Literacy Study (ICILS 2013) provides, for the first time, information about students’ computer and information literacy (CIL), as well as its acquisition, based on a computer-based test for students and background questionnaires. Among the 21 education systems that participated in ICILS 2013, there are 12 European countries, making secondary comparative in-depth analyses at a European level particularly fruitful. Accordingly, while the four articles in this Special Issue each deal with different topics and adopt different methodologies, they all share a common element and provide European comparisons in the ICILS context. The editorial in turn outlines the aim of the ICILS 2013 study and its relevance for European education research as well as its contextual framework and approach to the measurement of students’ CIL. The potential and challenges of such large-scale assessment studies are also discussed.

The Use of Tablets in Secondary Schools and Its Relationship with Computer Literacy - Drossel, Kerstin; Eickelmann, Birgit (Tomorrow's learning: involving everyone. Learning with and about technologies and computing)

Schulische Medienkompetenzförderung - Eickelmann, Birgit (Medienkompetenz. Herausforderung für Politik, politische Bildung und Medienbildung)

Понять, как они тикают [Verstehen, wie sie ticken]. Interview on CLIL conducted by Ирина Долженко [Irina Dolzhenko] on behalf of sib.fm - Dolzhenko, Irina; Rumlich, Dominik

Unter welchen Voraussetzungen kooperieren Grundschullehrkräfte im inklusiven Unterricht? Eine Studie zu den Bedingungen der Kooperationsbereitschaft von Grundschullehrerinnen und -lehrern im inklusiven Unterricht - Hellmich, Frank; Hoya, Fabian Karl; Görel, Gamze; Schwab, Susanne (Empirische Sonderpädagogik)
Als wichtige Bedingungen für die Realisierung inklusiven Unterrichts in der Grundschule gelten Kooperationen von Grund- und Sonderschullehrkräften. Bislang ist wenig darüber bekannt, unter welchen Voraussetzungen Grundschullehrkräfte Bereitschaft zur Kooperation im inklusiven Unterricht zeigen. Vor diesem Hintergrund haben wir 168 Grundschullehrkräfte einerseits zu ihrer Kooperationsbereitschaft im inklusiven Unterricht und andererseits zu ihren Einstellungen zur Inklusion und zur Teamarbeit, ihren Erfahrungen aus dem integrativen bzw. inklusiven Unterricht sowie ihren Selbstwirksamkeitsüberzeugungen für die Gestaltung des inklusiven Unterrichts befragt. Die Ergebnisse aus einem Strukturgleichungsmodell geben Hinweise auf die Bedeutungen der Einstellungen zur Teamarbeit und der Erfahrungen aus dem integrativen bzw. inklusiven Unterricht für die Kooperationsbereitschaft der Grundschullehrkräfte. (DIPF/Orig.)

Motivation für die Beschäftigung mit Inklusion während des Studiums bei Studierenden des Lehramts an Grundschulen - Hellmich, Frank; Görel, Gamze; Schwab, Susanne (Profession und Disziplin - Grundschulpädagogik im Diskurs)

Erfahrungen, Einstellungen und Motivation von Studierenden des Grundschullehramts in Hinblick auf den inklusiven Unterricht. - Görel, Gamze; Hellmich, Frank (Sonderpädagogik zwischen Wirksamkeitsforschung und Gesellschaftskritik)

Self-efficacy of prospective Austrian and German primary school teachers regarding the implementation of inclusive education - Schwab, Susanne; Hellmich, Frank; Görel, Gamze (Journal of Research in Special Educational Needs)

Einstellungen von Kindern gegenüber Peers mit sonderpädagogischem Förderbedarf als Bedingungen der sozialen Partizipation im inklusiven Unterricht der Grundschule - Hellmich, Frank; Löper, Marwin Felix; Görel, Gamze; Pfahl, Rebecca (Inklusiver Unterricht in der Grundschule)

Primary school students’ implicit theories and their reading motivation. The role of parents’ and teachers’ effort feedback - Hellmich, Frank; Hoya, Fabian Karl (Zeitschrift für Psychologie)
Abstract. Parents’ and teachers’ effort feedback is considered to be an important prerequisite for children’s implicit theories of intelligence and their academic self-concepts as well as for their learning and achievement motivation. Therefore, our study examines whether differences in N = 685 primary school students’ implicit theories, their reading self-concepts, and their reading motivation can be predicted by their perceptions of their parents’ and teachers’ effort feedback on reading processes. The results of a structural equation model show that children’s perceptions of their parents’ effort feedback predict their implicit theories, their reading self-concepts, and their reading motivation. The correlation between children’s perceived parental effort feedback and their intrinsic reading motivation is mediated by their implicit theories. Children’s implicit theories and their reading motivation cannot be predicted by their perceptions of their teachers’ effort feedback.

Empirische Arbeit: Wahrgenommenes positives Feedback zu Leseprozessen in Elternhaus und Schule im Zusammenhang mit der Lesemotivation von Kindern im Grundschulalter - Hellmich, Frank; Hoya, Fabian Karl (Psychologie in Erziehung und Unterricht)

Soziale Selbstkonzepte von Kindern im Grundschulalter und ihre Einstellungen gegenüber Peers mit Förderbedarf in der sozial-emotionalen Entwicklung - Löper, Marwin Felix; Hellmich, Frank (Sonderpädagogik zwischen Wirksamkeitsforschung und Gesellschaftskritik)

Inklusiver Unterricht in der Grundschule

Decision Taking, Confidence and Risk Management in Banks from Early Modernity to the 20th Century

Human agency at work: An active approach towards expertise development - Goller, Michael
Michael Goller gives a structured overview of the current discourses of human agency in relation to professional learning and development. Based on this discussion, the author develops a theoretical framework including human agency as an individual feature (i. e., a disposition) as well as a set of self-initiated and goal-directed behaviours that are assumed to affect employees’ learning and development (e. g., crafting of new work experiences). He then further specifies this theoretical framework and investigates it empirically in the domain of geriatric care nursing. Based on the findings of the three empirical studies conducted, the author discusses the relevance of human agency for the development of professional expertise of geriatric care nurses. The work received the American Educational Research Association (AERA) Workplace Learning SIG 2017 Dissertation of the Year Award.
Keywords: Workplace learning; Agency; Expertise

Intuition as Crucial Component of Professional Competence: Its Relevance for Competence-based Vocational and Professional Education and Training - Harteis, Christian (Competence-based Vocational and Professional Education)

Emotions, coping and learning in error situations in the workplace - Rausch, Andreas; Seifried, Jürgen; Harteis, Christian (Journal of Workplace Learning)

Human agency at work: Towards a clarification and operationalisation of the concept - Goller, Michael; Harteis, Christian (Agency at Work)

Learning from errors in workplace settings - Harteis, Christian; Gartmeier, Martin (Journal of Workplace Learning)

Epistemische Überzeugungen Beschäftigter und ihre Bedeutung für berufliches Lernen - Harteis, Christian; Festner, Dagmar; Bauer, Johannes (Wissen und Lernen. Wie epistemische Überzeugungen Schule, Universität und Arbeitswelt beeinflussen)

Digitalisierung in der Schule (Lernende Schule)

Multiprofessionelle Kooperation in der Schule: Forschungsbefunde und Handlungsperspektiven für Schulleitungen - Drossel, Kerstin; Gröhlich, Carola (Schulmanagement)

Predictors of Teachers’ Use of ICT in School – the Relevance of School Characteristics, Teachers’ Attitudes and Teacher Collaboration - Drossel, Kerstin; Eickelmann, Birgit; Gerick, Julia (Education and Information Technologies)

Determinants of teachers’ collaborative use of information and communications technology for teaching and learning: A European perspective - Drossel, Kerstin; Eickelmann, Birgit; Schulz-Zander, Renate (European Educational Research Journal)

Rezension des Buches von Jasmin Bastian und Stefan Aufenanger: Tablets in Schule und Unterricht. Forschungsergebnisse zum Einsatz digitaler Medien - Drossel, Kerstin (Journal für Schulentwicklung)

Teachers’ participation in professional development concerning the implementation of new technologies in class: a latent class analysis of teachers and the relationship with the use of computers, ICT self-efficacy and emphasis on teaching ICT skills - Drossel, Kerstin; Eickelmann, Birgit (Large-scale Assessments in Education)

Digitale Bildung – ein neue Perspektive auf Bildungsgerechtigkeit? - Eickelmann, Birgit; Drossel, Kerstin (Dreizehn - Zeitschrift für Jugendsozialarbeit)

Computer- und informationsbezogene Kompetenzen in der IEA Studie ICILS 2013 und der Zusammenhang mit der Lesekompetenz - Eickelmann, Birgit; Drossel, Kerstin (Medienimpulse)
Der kompetente Umgang mit Informations- und Kommunikationstechnologien (ICT) gewinnt im Zuge des Wandels zur Informations- und Wissensgesellschaft zunehmend an Bedeutung. Die International Computer and Information Literacy Study (ICILS 2013) erfasst in diesem Zusammenhang erstmals computer- und informationsbezogene Kompetenzen computerbasiert im internationalen Vergleich. Theoretische Überlegungen und empirische Befunde postulieren dabei einen Zusammenhang der erfassten Kompetenzdomäne mit der Lesekompetenz der Schülerinnen und Schüler. Eine empirische Untersuchung dieses Zusammenhangs steht bislang allerdings noch aus und ist das Anliegen dieses Beitrags. Um diesem Desiderat nachzugehen, werden die repräsentativen Schülerdaten aus ICILS 2013 für Deutschland herangezogen. Dabei wird die Untersuchung des Zusammenhangs der beiden Konstrukte möglich, da in Deutschland national ein Lesetest ergänzt wurde, den die Achtklässlerinnen und Achtklässler zusätzlich bearbeitet haben. Die Pfadanalyse zeigt, dass Lesen einen mittleren direkten Effekt von .452 auf die computer- und informationsbezogenen Kompetenzen aufweist.

The Use of Tablets in Secondary Schools and Its Relationship with Computer Literacy - Drossel, Kerstin; Eickelmann, Birgit (Tomorrow's Learning: Involving Everyone. Learning with and about Technologies and Computing)

Internet of Things Architecture for Handling Stream Air Pollution Data - Kersting, Joschka; Geierhos, Michaela; Jung, Hanmin; Kim, Taehong (Proceedings of the 2nd International Conference on Internet of Things, Big Data and Security)
In this paper, we present an IoT architecture which handles stream sensor data of air pollution. Particle pollution is known as a serious threat to human health. Along with developments in the use of wireless sensors and the IoT, we propose an architecture that flexibly measures and processes stream data collected in real-time by movable and low-cost IoT sensors. Thus, it enables a wide-spread network of wireless sensors that can follow changes in human behavior. Apart from stating reasons for the need of such a development and its requirements, we provide a conceptual design as well as a technological design of such an architecture. The technological design consists of Kaa and Apache Storm which can collect air pollution information in real-time and solve various problems to process data such as missing data and synchronization. This enables us to add a simulation in which we provide issues that might come up when having our architecture in use. Together with these issues, we state r easons for choosing specific modules among candidates. Our architecture combines wireless sensors with the Kaa IoT framework, an Apache Kafka pipeline and an Apache Storm Data Stream Management System among others. We even provide open-government data sets that are freely available.
Keywords: Wireless Sensor Network; Internet of Things; Stream Data; Air Pollution; DSMS; Real-time Data Processing

Annotation Challenges for Reconstructing the Structural Elaboration of Middle Low German - Seemann, Nina; Merten, Marie-Luis; Geierhos, Michaela; Tophinke, Doris; Hüllermeier, Eyke (Proceedings of the Joint SIGHUM Workshop on Computational Linguistics for Cultural Heritage, Social Sciences, Humanities and Literature)
In this paper, we present the annotation challenges we have encountered when working on a historical language that was undergoing elaboration processes. We especially focus on syntactic ambiguity and gradience in Middle Low German, which causes uncertainty to some extent. Since current annotation tools consider construction contexts and the dynamics of the grammaticalization only partially, we plan to extend CorA – a web-based annotation tool for historical and other non-standard language data – to capture elaboration phenomena and annotator unsureness. Moreover, we seek to interactively learn morphological as well as syntactic annotations.

Using Sentiment Analysis on Local Up-to-the-Minute News: An Integrated Approach - Kersting, Joschka; Geierhos, Michaela (Information and Software Technologies: 23rd International Conference, ICIST 2017, Druskininkai, Lithuania, October 12–14, 2017, Proceedings)
In this paper, we present a search solution that makes local news information easily accessible. In the era of fake news, we provide an approach for accessing news information through opinion mining. This enables users to view news on the same topics from different web sources. By applying sentiment analysis on social media posts, users can better understand how issues are captured and see people’s reactions. Therefore, we provide a local search service that first localizes news articles, then visualizes their occurrence according to the frequency of mentioned topics on a heatmap and even shows the sentiment score for each text.

Privacy Matters: Detecting Nocuous Patient Data Exposure in Online Physician Reviews - Bäumer, Frederik Simon; Grote, Nicolai; Kersting, Joschka; Geierhos, Michaela (Information and Software Technologies: 23rd International Conference, ICIST 2017, Druskininkai, Lithuania, October 12–14, 2017, Proceedings)
Consulting a physician was long regarded as an intimate and private matter. The physician-patient relationship was perceived as sensitive and trustful. Nowadays, there is a change, as medical procedures and physicians consultations are reviewed like other services on the Internet. To allay user’s privacy doubts, physician review websites assure anonymity and the protection of private data. However, there are hundreds of reviews that reveal private information and hence enable physicians or the public to identify patients. Thus, we draw attention to the cases when de-anonymization is possible. We therefore introduce an approach that highlights private information in physician reviews for users to avoid an accidental disclosure. For this reason, we combine established natural-language-processing techniques such as named entity recognition as well as handcrafted patterns to achieve a high detection accuracy. That way, we can help websites to increase privacy protection by recognizing and uncovering apparently uncritical information in user-generated texts.
Keywords: Physician Reviews; User Privacy; Nocuous Data Exposure

An annotated video corpus of interactions dealing with the collaborative construction of fiction in games - Menke, Peter (Proceedings of the Corpus Linguistics Conference 2017)

Proceedings of the BHQFHE projects. Basis, Analysis, Development, Impact and Prosepcts of the BHQFHE Tempus Project

Chosen - Mindt, Ilka (Zeitschrift für Anglistik und Amerikanistik)

Analyzing Corpus Data from Within - Mindt, Ilka (Anglistik. International Journal of English Studies)

Accreditation of Study Programs - Mindt, Ilka (Proceedings of the BHQFHE projects. Basis, Analysis, Development, Impact and Prosepcts of the BHQFHE Tempus Project)

studiolo communis, Einleitung - Seng, Eva- Maria (studiolo. Kooperative Forschungsumgebungen in den eHumanities)

Konstellationsforschung als methodischer Ansatz für kooperative Forschungsumgebungen in der Kunst- und Architekturgeschichte - Seng, Eva- Maria (studiolo. Kooperative Forschungsumgebungen in den eHumanities)

Forschungen zu Städtebau und Kirchenbau - Seng, Eva- Maria (Mitteilungen zur Kirchlichen Zeitgeschichte 11/2017)

Die UNESCO-Konvention zur Erhaltung des immateriellen Kulturerbes - Seng, Eva- Maria (Heimatpflege in Westfalen)

Urbanistische Projekte in Stuttgart zur Zeit Carl Eugens - Seng, Eva- Maria (Aufgeklärte Herrschaft im Konfikt. Herzog Carl Eugen von Württemberg 1728-1793 (Geschichte Württembergs. Impulse der Forschung. Schriftenreihe des württembergischen Geschichts- und Altertumsvereins Hg. von Nicole Bickhoff, Bd. 1))

- Utopie und Architektur zu Beginn des 21. Jahrhunderts. Dave Eggers’ Utopie der totalen Vernetzung – Branding und Firmenarchitektur: Der Firmencampus als Utopos - Seng, Eva- Maria (Auf Utopias Spuren. Utopie und Utopieforschung. Festschrift für Richard Saage zum 75. Geburtstag)

Herta Müller-Handbuch

Margarete-Schrader-Preis für Literatur der Universität Paderborn. Dokumentation der Verleihung an Jörg Albrecht am 9. Februar 2017

“Schnee. Eiszeit.” Kälte – eine Konstellation im Werk Heiner Müllers - Eke, Norbert Otto (Ich bin meiner Zeit voraus. Utopie und Sinnlichkeit bei Heiner Müller)

Erinnerte Größe. Ambigue „Napoleono-Manie“ im Vormärz - Eke, Norbert Otto (Interférence littéraires/Literaire interferenties 20: The Reception of Waterloo in the 19th Century, June 2017)

Herta Müller: Biographische Skizze - Eke, Norbert Otto (Herta Müller-Handbuch)

Oskar Pastior [und Herta Müller] - Eke, Norbert Otto (Herta Müller-Handbuch)

Utopie - Eke, Norbert Otto (Herta Müller-Handbuch)

Auswahlbibliographie [zu Herta Müller] - Eke, Norbert Otto (Herta Müller-Handbuch)

„Party hieß früher: Exzesse ausführen, und jetzt? Mit Ach und Krach Exzesse aufführen.“ Laudatio zur Verleihung des Margarete-Schrader-Literaturpreises der Universität Paderborn an Jörg Albrecht am 09.02.2017 - Eke, Norbert Otto (Margarete-Schrader-Preis für Literatur der Universität Paderborn. Dokumentation der Verleihung an Jörg Albrecht am 9. Februar 2017)

E-Assessments in der Hochschulpraxis. Empfehlungen zur Verankerung von E-Assessments in NRW - Meister, Dorothee M.; Oevel, Gudrun

Aufwachsen und lernen mit Medien - Meise, Bianca; Meister, Dorothee M. (Digitale Medien im Musikunterricht. Bestandsaufnahme Reflexion Perspektiven. Kongress „Musikunterricht und Multimedia“ an der Niedersächsischen Landesmusikakademie Wolfenbüttel 20.-21. Mai 2016)

Digitale Transformationen. Zum Einfluss der Digitalisierung auf die musikwissenschaftliche Editionsarbeit - Meise, Bianca; Meister, Dorothee M. (medien + erziehung (merz))

Medienarbeit mit Gelüchteten - Meister, Dorothee M. (Software takes command. Herausforderungen der "Datafizierung" für die Medienpädagogik in Theorie und Praxis)

"Futurelab Medienpädagogik: Qualitätsentwicklung - Professionalisierung - Standards. Thesenpapier zum Forum Kommunikationskultur der GMK - Knaus, Thomas; Meister, Dorothee M.; Tulodziecki, Gerhard (MedienPädagogik, (24. Oktober))

Medienpädagogik: Herausforderungen der Digitalisierung - Meister, Dorothee M. (Kulturelle Bildung digital - Vermittlungsformen, ästhetische Praxis und Aus- und Weiterbildung, Dossier 6)

Berufliche Bildung - Kamin, Anna-Maria; Meister, Dorothee M. (Grundbegriffe Medienpädagogik)

Medienpädagogik - von Gross, F.; Meister, Dorothee M.; Sander, U. (Lexikon der Kunstpädagogik)

Digital unterstütztes Lernen in Pflegeberufen unter entgrenzten Bedingungen – Ein gestaltungs- und entwicklungsorientiertes Forschungsprojekt - Kamin, A.-M.; Meister, Dorothee M. (Digital und vernetzt: Lernen heute. Gestaltung von Lernumgebungen mit digitalen Medien unter entgrenzten Bedingungen)

Chosen - Mindt, Ilka (Zeitschrift für Anglistik und Amerikanistik)

Analyzing Corpus Data from Within - Mindt, Ilka (Anglistik. International Journal of English Studies)

CLIL theory and empirical reality – Two sides of the same coin? - Rumlich, Dominik (Journal of Immersion and Content-Based Language Education)

The rich environment of CLIL classes as an ideal setting for collaborative learning - Rumlich, Dominik; Ahlers, Sabine (Collaborative learning and new media)

Guesswork? Resolving Vagueness in User-Generated Software Requirements - Geierhos, Michaela; Bäumer, Frederik Simon (Partiality and Underspecification in Information, Languages, and Knowledge)
In recent years, there has been a proliferation of technological developments that incorporate processing of human language. Hardware and software can be specialized for designated subject areas, and computational devices are designed for a widening variety of applications. At the same time, new areas and applications are emerging by demanding intelligent technology enhanced by the processing of human language. These new applications often perform tasks which handle information, and they have a capacity to reason, using both formal and human language. Many sub-areas of Artificial Intelligence demand integration of Natural Language Processing, at least to some degree. Furthermore, technologies require coverage of known as well as unknown agents, and tasks with potential variations. All of this takes place in environments with unknown factors. The book covers theoretical work, advanced applications, approaches, and techniques for computational models of information, reasoning systems, and presentation in language. The book promotes work on intelligent natural language processing and related models of information, thought, reasoning, and other cognitive processes. The topics covered by the chapters prompt further research and developments of advanced systems in the areas of logic, computability, computational linguistics, cognitive science, neuroscience of language, robotics, and artificial intelligence, among others.

Studying Software Descriptions in SourceForge and App Stores for a better Understanding of real-life Requirements - Bäumer, Frederik Simon; Dollmann, Markus; Geierhos, Michaela (Proceedings of the 2nd ACM SIGSOFT International Workshop on App Market Analytics)
Users prefer natural language software requirements because of their usability and accessibility. Many approaches exist to elaborate these requirements and to support the users during the elicitation process. But there is a lack of adequate resources, which are needed to train and evaluate approaches for requirement refinement. We are trying to close this gap by using online available software descriptions from SourceForge and app stores. Thus, we present two real-life requirements collections based on online-available software descriptions. Our goal is to show the domain-specific characteristics of content words describing functional requirements. On the one hand, we created a semantic role-labeled requirements set, which we use for requirements classification. On the other hand, we enriched software descriptions with linguistic features and dependencies to provide evidence for the context-awareness of software functionalities.

On the origin of annotations: A module-based approach to representing annotations in the Natural Language Processing Interchange Format (NIF) - Menke, Peter; Ell, Basil; Cimiano, Philipp (Applied Ontology)

Indikatorbasierte Erkennung und Kompensation von ungenauen und unvollständig beschriebenen Softwareanforderungen - Bäumer, Frederik Simon
The vision of OTF Computing is to have the software needs of end users in the future covered by an automatic composition of existing software services. Here we focus on natural language software requirements that end users formulate and submit to OTF providers as requirement specifications. These requirements serve as the sole foundation for the composition of software; but they can be inaccurate and incomplete. Up to now, software developers have identified and corrected these deficits by using a bidirectional consolidation process. However, this type of quality assurance is no longer included in OTF Computing - the classic consolidation process is dropped. This is where this work picks up, dealing with the inaccuracies of freely formulated software design requirements. To do this, we developed the CORDULA (Compensation of Requirements Descriptions Using Linguistic Analysis) system that recognizes and compensates for language deficiencies (e.g., ambiguity, vagueness and incompleteness) in requirements written by inexperienced end users. CORDULA supports the search for suitable software services that can be combined in a composition by transferring requirement specifications into canonical core functionalities. This dissertation provides the first-ever method for holistically recording and improving language deficiencies in user-generated requirement specifications by dealing with ambiguity, incompleteness and vagueness in parallel and in sequence.

Narrative Ethics and Dementia in Alice LaPlante’s Turn of Mind - Strauß, Sara (Dementia and Subjectivity. Aesthetic, Literary and Philosophical Perspectives)

Introduction - Strauß, Sara (Dementia and Subjectivity. Aesthetic, Literary and Philosophical Perspectives)

Neuroethical Reflections on Body and Awareness in Kazuo Ishiguro’s Never Let Me Go and Ian McEwan’s Saturday - Strauß, Sara (Presence of the Body: Awareness In and Beyond Experience)

The Immobility of Power in British Political Theatre after 2000: Absurdist Dystopias - Tönnies, Merle (Journal of Contemporary Drama in English)

Still/Again 'Political'? New Approaches to Questioning Power in Mike Bartlett's 13 (2011) - Tönnies, Merle (Finance, Terror, and Science on Stage. Current Public Concerns in 21st-Century British Drama)

Pope, G.: Reading London's Suburbs - Tönnies, Merle (Anglistik. International Journal of English Studies)

From User Demand to Software Service: Using Machine Learning to Automate the Requirements Specification Process - van Rooijen, Lorijn; Bäumer, Frederik Simon; Platenius, Marie Christin; Geierhos, Michaela; Hamann, Heiko; Engels, Gregor (2017 IEEE 25th International Requirements Engineering Conference Workshops (REW))
Bridging the gap between informal, imprecise, and vague user requirements descriptions and precise formalized specifications is the main task of requirements engineering. Techniques such as interviews or story telling are used when requirements engineers try to identify a user's needs. The requirements specification process is typically done in a dialogue between users, domain experts, and requirements engineers. In our research, we aim at automating the specification of requirements. The idea is to distinguish between untrained users and trained users, and to exploit domain knowledge learned from previous runs of our system. We let untrained users provide unstructured natural language descriptions, while we allow trained users to provide examples of behavioral descriptions. In both cases, our goal is to synthesize formal requirements models similar to statecharts. From requirements specification processes with trained users, behavioral ontologies are learned which are later used to support the requirements specification process for untrained users. Our research method is original in combining natural language processing and search-based techniques for the synthesis of requirements specifications. Our work is embedded in a larger project that aims at automating the whole software development and deployment process in envisioned future software service markets.
Keywords: Software; Unified modeling language; Requirements engineering; Ontologies; Search problems; Natural languages

Dementia and Subjectivity. Aesthetic, Literary and Philosophical Perspectives

Fragments of a Life Remembered: Fragmentation and Silences in Dementia Narratives - Strauß, Sara (Narrative and Mental Health)

Semantic Annotation of Software Requirements with Language Frame - Kim, Yeong-Su; Lee, Seung-Woo; Dollmann, Markus; Geierhos, Michaela (International Journal of Software Engineering for Smart Device)
An end user generally writes down software requirements in ambiguous expressions using natural language; hence, a software developer attuned to programming language finds it difficult to understand th meaning of the requirements. To solve this problem we define semantic categories for disambiguation and classify/annotate the requirement into the categories by using machine-learning models. We extensively use a language frame closely related to such categories for designing features to overcome the problem of insufficient training data compare to the large number of classes. Our proposed model obtained a micro-average F1-score of 0.75, outperforming the previous model, REaCT.
Keywords: Natural Language Processing; Semantic Annotation; Machine Learning

The Renewal of British Political Theater in the Twenty-First Century: Indirect Narrative Approaches to Ideology and Power - Tönnies, Merle (Storyworlds: A Journal of Narrative Studies)

Ansprache - Peckhaus, Volker (Verleihung der Ehrendoktorwürde an den Herrn Bundesminister des Auswärtigen Dr. Frank-Walter Steinmeier durch die Fakultät für Kulturwissenschaften am 29. Dezember 2016)

Geschlechter-Macht-Binarismen relativiert: Margaret Atwoods Männerdarstellungen in "The Handmaid's Tale" - Hannebohm, Ronja (Geschlechter-Dramen: literarische und filmische Inszenierungen von 1800 bis heute)

„Nichts mehr stimmt, und alles ist wahr.“ Tabubrüche in Herta Müllers Atemschaukel - Willeke, Stephanie (Ästhetik des Tabuisierten in der Literatur- und Kulturgeschichte)

Shoah und Gulag - Willeke, Stephanie (Herta Müller-Handbuch)

Das Radikale – gesellschafts-politische und formal-ästhetische Aspekte. Eine Einführung - Willeke, Stephanie (Das Radikale – gesellschafts-politische und formal-ästhetische Aspekte in der Gegenwartsliteratur)